2012
DOI: 10.1590/s1516-35982012000300006
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, utilization efficiency and sward targets for mixed pastures of marandugrass, forage peanut and tropical kudzu

Abstract: -This study was carried out to evaluate the productivity and utilization efficiency of a mixed marandugrass (Brachiaria brizantha cv. Marandu), forage peanut (Arachis pintoi cv. Mandobi) and tropical kudzu (Pueraria phaseoloides) pasture, rotationally stocked at four daily forage allowance levels (6.6, 10.3, 14.3 and 17.9% of live weight), in order to define sward management targets for these mixtures. In each stocking cycle, dry matter (DM) accumulation rates, defoliation intensity (%), grazing depth (%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
(16 reference statements)
0
13
0
1
Order By: Relevance
“…The introduction of a forage legume such as Stylosanthes spp. or forage groundnut (Arachis pintoi) into these pastures has been shown to be very effective in increasing pasture yields and animal weight gains (Vilela and Ayarza, 2002;Andrade et al, 2012) although adoption has been poor, as very careful management is required for the legume to persist in the sward. The great advantage of the legume is the complete elimination of the GHG emissions (fossil CO 2 from natural gas) associated with the manufacture and application of N fertilizer (Robertson and Grace, 2004) and possibly lower N 2 O emissions.…”
Section: Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of a forage legume such as Stylosanthes spp. or forage groundnut (Arachis pintoi) into these pastures has been shown to be very effective in increasing pasture yields and animal weight gains (Vilela and Ayarza, 2002;Andrade et al, 2012) although adoption has been poor, as very careful management is required for the legume to persist in the sward. The great advantage of the legume is the complete elimination of the GHG emissions (fossil CO 2 from natural gas) associated with the manufacture and application of N fertilizer (Robertson and Grace, 2004) and possibly lower N 2 O emissions.…”
Section: Scenariomentioning
confidence: 99%
“…In tropical regions, most production is on unfertilized pastures of grasses of African origin, mainly Brachiaria spp. Large responses in animal live weight gain (LWG) can be obtained with applications of nitrogen (N) and phosphorus (P) fertilizer or with the introduction of forage legumes (Euclides Filho et al, 2002;Andrade et al, 2012). The manufacture of fertilizers, especially N, requires significant fossil fuel inputs and hence increases the overall GHG emissions of the production systems.…”
Section: Introductionmentioning
confidence: 99%
“…In Acre state (Amazon biome), improved grass-legume pastures of Massai grass-forage peanut managed under rotational stocking had an average carrying capacity of 3.6 AU/ha during the rainy season and 1.8 AU/ha during the dry season (Andrade et al, 2006). Rotationally grazed pastures of Marandu grass mixed with forage peanut and tropical kudzu had an average annual carrying capacity of 2.5 AU/ha (Andrade et al, 2012), which is also higher than the state average (Valentim and Andrade, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Assis et al (2008) evaluated 21 genotypes of pinto peanut and observed that the dry matter production varied from 1,609 to 4,132 kg/ha.year, and the Belmonte cultivar was a highlight among all genotypes. It is worthy to note that the mix between Belmonte cultivar and the forage grasses has increased the productivity and profitability of the systems where it is already in use (Andrade et al, 2012;Oliveira, 2007). Fialho (2015) studying the characteristics of A. pintoi cv.…”
Section: Pinto Peanut (A Pintoi)mentioning
confidence: 99%